Emidio Santana : inter-departmental correspondence - Santana, Emídio; Bolton, W. J.
016b-0037-001 I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From W.J. BOLTON. Department. INTERNATIONAL. To SIR WALTER CITRINE. Date 18 October 1937. SUBJECT. EMIDIO SANTANA. Upon telephoning the Home Office (Mr. Ralph, Chief Immigration Officer) we were informed that representations had already been made by Mr. Attlee in regard to this case, and also that the "Secretary of State had called for the files". Mr. Ralph informed us that this man, Emidio Santana, was a stowaway, had arrived without a passport or papers, and had been prosecuted by the shipping company. He had thereupon paid the Company for his passage, and had been put on a ship, which left Southampton on Saturday last, sailing to Cherbourg and Portugal. He had informed the Immigration Officials at Southampton that he had no intention of coming to England, but had been compelled to do so owing to there being some difficulties in his way of landing at Cherbourg. He communicated with his friends during his stay in Southampton asking them to forward his papers to him at Southampton if they could reach him before Saturday, and if not, to address them to him at Cherbourg. As they had not arrived up to the time of his departure, it was assumed that they would be waiting him at Cherbourg. 292/946/16b/41